Building the Personality of a Humble Educator: A Thematic Review of the Prophet's Hadith - Siti Ria Wahyuni; Muhid (Konsultan Jurnal Ilmiah Indonesia, 2025)
This study aims to analyze the role of tawadhu’ (humility) values in the Prophet’s hadiths in shaping educators’ personalities. Employing qualitative library research, the study examines various literature and key prophetic narrations on humility. The thematic analysis reveals tawadhu’ as a multidimensional concept encompassing equality, gentleness, non-superiority, and appreciation of differences supported by major hadiths such as HR. Muslim no. 2588, 91, and 2865. Findings show that incorporating tawadhu’ in teaching practice involves: (1) fostering dialogic space; (2) avoiding arrogance; (3) respecting students; (4) pursuing lifelong learning; and (5) teaching with sincere intentions. The study concludes that integrating tawadhu’ into educational settings cultivates educators who are both academically competent and morally upright, thus fostering inclusive, harmonious, and spiritually enriched learning environments.